2021
DOI: 10.1038/s41467-021-24535-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of mESC-derived tendon and fibrocartilage cell fate switch

Abstract: The transcriptional regulators underlying induction and differentiation of dense connective tissues such as tendon and related fibrocartilaginous tissues (meniscus and annulus fibrosus) remain largely unknown. Using an iterative approach informed by developmental cues and single cell RNA sequencing (scRNA-seq), we establish directed differentiation models to generate tendon and fibrocartilage cells from mouse embryonic stem cells (mESCs) by activation of TGFβ and hedgehog pathways, achieving 90% induction effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 99 publications
4
26
0
Order By: Relevance
“…Interestingly, both tenogenic (Scx, Tnmd, and Mkx) and chondrogenic (Sox9, Acan, Col2a1, and Col11a1) markers were significantly upregulated when BMS493 and TGF-β2 were added (Figure 8C). Since ATRA has been reported to suppress fibrocartilage differentiation (Kaji et al, 2021) which is characterized by induction of cells simultaneously expressing Col1 and Col2 but negative for Tnmd (Benjamin and Evans, 1990;Sugimoto et al, 2013a), our results suggest that both tenogenic and fibrocartilaginous chondrogenic differentiation are negatively regulated by activation of RA signaling. We next investigated the relation between endogenous RA signaling and tenogenic/chondrogenic differentiation by analyzing the expression status of Scx and Aldh1a2 in our single cell analysis.…”
Section: Retinoic Acid Negatively Regulated Induction Of Scx + Cells ...mentioning
confidence: 59%
See 2 more Smart Citations
“…Interestingly, both tenogenic (Scx, Tnmd, and Mkx) and chondrogenic (Sox9, Acan, Col2a1, and Col11a1) markers were significantly upregulated when BMS493 and TGF-β2 were added (Figure 8C). Since ATRA has been reported to suppress fibrocartilage differentiation (Kaji et al, 2021) which is characterized by induction of cells simultaneously expressing Col1 and Col2 but negative for Tnmd (Benjamin and Evans, 1990;Sugimoto et al, 2013a), our results suggest that both tenogenic and fibrocartilaginous chondrogenic differentiation are negatively regulated by activation of RA signaling. We next investigated the relation between endogenous RA signaling and tenogenic/chondrogenic differentiation by analyzing the expression status of Scx and Aldh1a2 in our single cell analysis.…”
Section: Retinoic Acid Negatively Regulated Induction Of Scx + Cells ...mentioning
confidence: 59%
“…Tnmd is a widely accepted molecular marker of mature tenocytes ( Shukunami et al, 2006 ). Recent studies have also reported the induction of tenogenic cells from ScxGFP pluripotent cells by activation of TGF-β signaling using TGF-β1 ( Komura et al, 2020 ; Kaji et al, 2021 ). In the developing mouse limb, Tgfb2 was reported to show the highest level of expression compared to those of other Tgfb genes ( Havis et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research explains this in more detail. It was demonstrated that RA initially contribute to the regulation of tendon progenitors, with mESCs undergoing neural differentiation when RA signaling is activated, while differentiating into tendon progenitors of paraxial mesoderm when RA signaling is inhibited ( Kaji et al, 2021 ). RA further regulates tendon progenitor cells, differentiating into the tenogenic lineage when RA signaling is activated, with reverse differentiation into fibrocartilage ( Kaji et al, 2021 ).…”
Section: Formation and Development Of Tendonsmentioning
confidence: 99%
“…It was demonstrated that RA initially contribute to the regulation of tendon progenitors, with mESCs undergoing neural differentiation when RA signaling is activated, while differentiating into tendon progenitors of paraxial mesoderm when RA signaling is inhibited ( Kaji et al, 2021 ). RA further regulates tendon progenitor cells, differentiating into the tenogenic lineage when RA signaling is activated, with reverse differentiation into fibrocartilage ( Kaji et al, 2021 ). Besides, it was found that the variations of retinoids concentration in endogenous local region promoted the formation of tendon condensations and attachment sites within the extraocular area ( Comai et al, 2020 ).…”
Section: Formation and Development Of Tendonsmentioning
confidence: 99%